Talkpal.AI: An Effective Vocabulary Learning Media in Class VIII D at MTs Salafiyah Syafi’iyah Seblak - M Rifqi Zanuar; Sayid Ma'rifatulloh (CV. Ulil Albab Corp, 2026)
The purpose of this study is to evaluate Talkpal's efficacy.AI as a vocabulary-learning tool for MTs Salafiyah Syafi'iyah Seblak students in Class VIII D. A quantitative pre-experimental design including a pre-test and post-test was employed in this study. The pre-test scores ranged from 20 to 65, with a low mean score of 41.67. With scores ranging from 60 to 95, the post-test mean rose to 75.48 following the intervention. The results show that pupils' vocabulary mastery has significantly improved. Thus, Talkpal.AI is regarded as a cutting-edge and successful tool for improving language acquisition.